Literature review: treatment design to overcome anticancer drug resistance - Udin, Baha; Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Rizkiana, Muhammad Dinta (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
One of the main causes of death in the world today is cancer. Chemotherapy is one treatment that cancer patients may utilize. Anticancer medication resistance, which might forecast a rise in treatment failure rates among cancer patients, poses a challenge to the current use of anticancer treatments. Numerous investigators have studied potential approaches to combat anti-cancer medication resistance. The purpose of this literature review is to provide information on treatment planning that can be applied to counteract anti-cancer medication resistance. Cancer is one of the leading causes of death in the modern world. One therapeutic option available to cancer patients is chemotherapy. The current usage of anticancer medicines is challenged by anticancer medication resistance, which may predict an increase in treatment failure rates among cancer patients. Many researchers have looked into possible strategies to fight drug resistance to anti-cancer medications. This review of the literature aims to give information on treatment planning that can be used to combat drug resistance to anti-cancer medications.